Investigating mass transport and recombination as a function of structural variation in dye-sensitized solar cells employing indole fused heterocyclic organic sensitizers and cobalt electrolytes - Jayadev V; Sourava C. Pradhan; P.R. Nitha; Jubi John; K.N. Narayanan Unni; Suraj Soman (Journal of Photochemistry and Photobiology, 2024)
Alternate cobalt redox mediator based dye-sensitized solar cells (DSCs) are getting widespread attention taking advantage of their one-electron transfer mechanism compared to the conventional iodide/triiodide electrolyte. In the present study, we used indole fused heterocyclic organic sensitizers having indolo[3,2-b]indole as donor with three different π-spacers [(benzene (IID-1), thiophene (IID-2) and furan (IID-3)] along with cobalt bipyridine derivatives as redox mediators having different peripheral substituents {[Co(bpy)3]3+/2+, [Co(Me2bpy)3]3+/2+, and [Co(t-Bu2bpy)3]3+/2+}. A detailed investigation was carried out to understand the fundamental charge transfer processes and loss mechanism happening at the various interfaces as a function of structural variations in the present dye-electrolyte combinations. Among the investigated systems, higher performance was obtained for the association of furan substituted dye (IID-3) with [Co(t-Bu2bpy)3]3+/2+ electrolyte. The importance of choosing the right combination of sensitizer and electrolyte is critical to realize higher performance in dye-sensitized solar cells particularly while employing organic dyes and alternate metal complex redox electrolytes which was systematically investigated in the present manuscript.